(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2020)
In pharmaceutical industry, statistically valid experimental design can be utilized to optimize data in order to provide an economic and effective formulation, which could overcome several product and process development problems. Domperidone is a BCS Class II drug and has wide range of use, but has very poor bioavailability when administered orally because of degradation in intestinal fluid. The present study was focused on formulation, evaluation and optimization of mucoadhesive tablets of domperidone using a four-factor, three-level Box-Behnken design (BBD) so as to retain the prepared optimized formulation in gastric fluid for a prolong period of time in order to have better bioavailability and to get a sustained action. Physicochemical properties of the prepared formulations were determined according to the USP pharmacopeia official method and found satisfactory, except friability which was optimized to get the acceptable value. In-vitro dissolution study was performed for 8 hours for all the prepared formulations using USP II (paddle type) dissolution tester having 0.1N HCl (pH 1.2) as dissolution medium. Obtained data was further analyzed by means of quadratic response surface models so as to find out an optimize formulation in terms of desirable condition of dissolution rate after 1 hour, after 8 hours, total mucoadhesion time and tablet friability. Optimized formulation was further evaluated and it was found that, it was almost similar to the proposed optimized data. The formulation can provide a high degree of patient compliance, as sustained release formulation reduces the side effects and the cost of the formulation will be minimal as lesser amount of effort will be needed employing statistical model instead of conventional trial and error method. Dhaka Univ. J. Pharm. Sci. 19(1): 65-76, 2020 (June)